2005
DOI: 10.1088/0953-8984/17/43/l02
|View full text |Cite
|
Sign up to set email alerts
|

The electron glass in a switchable mirror: relaxation, ageing and universality

Abstract: The rare earth hydride YH 3−δ can be tuned through the metal-insulator transition both by changing δ and by illumination with ultraviolet light. The transition is dominated by strong electron-electron interactions, with transport in the insulator sensitive to both a Coulomb gap and persistent quantum fluctuations. Via a systematic variation of UV illumination time, photon flux, separation between electrons, and temperature, we demonstrate that polycrystalline YH 3−δ serves as a model system for studying the pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…Recent experiments on indium oxides by Ovadyahu's group [1] have shown glassy behavior such as logarithmic relaxation and aging. Similar effects have also been found on granular metals [2], on ultrathin metal films [3], and on a rare earth hydride [4]. All of these systems can be quite well described by the Coulomb glass model, which keeps gaining importance in the study of glassy relaxation.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…Recent experiments on indium oxides by Ovadyahu's group [1] have shown glassy behavior such as logarithmic relaxation and aging. Similar effects have also been found on granular metals [2], on ultrathin metal films [3], and on a rare earth hydride [4]. All of these systems can be quite well described by the Coulomb glass model, which keeps gaining importance in the study of glassy relaxation.…”
supporting
confidence: 56%
“…After roughly t 100, a proper FD distribution is observed, independently of the initial configuration. We have checked that starting from an electron-hole asymmetric initial configuration, designed to reproduce experiments where the sample is excited with light [4], basically does not change the results.…”
mentioning
confidence: 99%
“…In a recent article [1], Lee et al reported interesting glassy behaviour in the relaxation of photoinduced conductivity in doped yttrium hydrides, YH 3−δ with δ ≈ 0.039. The relative decrease of the conductivity was found to be a scaling function of the ratio between the time t elapsed after the excitation, and the illumination time t w , δσ (t; t w )/ σ tot (t w ) = F(t/t w ), where σ tot (t w ) is the total excess conductivity induced by the illumination.…”
mentioning
confidence: 99%
“…0.1), such as the MIT, quantum glasses are even less understood than their classical counterparts. Experimental studies of charge or Coulomb glasses (Davies et al, 1982;Grünewald et al, 1982;Pollak and Ortuño, 1982;Davies et al, 1984;Pollak, 1984), which are of particular relevance to the MIT, have been relatively scarce (Monroe et al, 1987;Ben-Chorin et al, 1993;Ovadyahu and Pollak, 1997;Vaknin et al, 1998;Vaknin et al, 2000;Vaknin et al, 2002;Orlyanchik and Ovadyahu, 2004;Ovadyahu, 2006a;Ovadyahu, 2006b;Martinez-Arizala et al, 1997;Martinez-Arizala et al, 1998;Bielejec and Wu, 2001;Hernandez et al, 2003;Grenet, 2003;Lee et al, 2005;Grenet et al, 2007;Kar et al, 2003;Thorsmølle and Armitage, 2010), and mostly limited to insulating systems far from the MIT. Recent observations (Bogdanovich and Popović, 2002b;Bogdanovich and Popović, 2002a;Jaroszyński et al, 2002b;Jaroszyński et al, 2002a;Popović et al, 2003;Jaroszyński et al, 2004b;Jaroszyński et al, 2004a;Jaroszyński and Popović, 2006;Jaroszyński and Popović, 2007b;Jaroszyński and Popović, 2007a) of glassiness in a 2DES in Si MOSFETs near the MIT open up opportunities for exploring glassy phenomena in this important regime over a wide range of all the relevant parameters.…”
Section: Glassy Freezing Of Electrons In Two Dimensionsmentioning
confidence: 99%